FIGURATIVE LANGUAGE USED IN ED SHEERAN’S SELECTED SONGS - Heni, Monika; Pratiwi, Desak Putu Eka; Santika, I Dewa Ayu Devi Maharani (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis study concern with the descriptive analysis of figurative language found in EdSheeran’s selected songs. The study's objective is to describe the types of figurativelanguage and to analyze the meaning of figurative language. This study is expected toobtain the result that will be useful for the reader especially in knowing what figurativelanguage is and what types of figurative language are. The researcher used a descriptivequalitative method to classify and analyze based on the theory of Figurative LanguageProposed by Knickerbocker and Reninger (1963) and also the theory of Meaningproposed by Leech (1974). The result found that there are 14 sentences of six kinds offigurative language used in Ed Sheeran’s Selected songs, such as simile with 2 or 14%, ametaphor with 1 or 8%, personification with 3 or 21%, metonymy with 1or 8%, hyperbolewith 5 or 35%, irony with 2 or 14%,. It can be indicated that the dominant type offigurative language in the song lyrics is hyperbole. The meaning of figurative languageis also stated clearly. It can be concluded that figurative language has important roles increated the song lyric. Using figurative language makes the song more interesting. Thatis why the author used sentences that have figurative language in the song.Keywords: Figurative language, song lyrics and meaningABSTRAKPenelitian ini membahas tentang analisis deskriptif bahasa kiasan yang ditemukan dalamlagu-lagu pilihan Ed Sheeran. Tujuan penelitian ini adalah untuk mendeskripsikan jenisjenisbahasa kiasan dan menganalisis makna dari bahasa kiasan. Penelitian inidiharapkan memperoleh hasil yang bermanfaat bagi pembaca khususnya dalammengetahui apa itu bahasa kiasan dan apa saja jenis-jenis bahasa kiasan. Penelitimenggunakan metode deskriptif kualitatif untuk mengklasifikasi dan menganalisisberdasarkan teori Bahasa Figuratif yang dikemukakan oleh Knickerbocker dan Reninger(1963) dan juga teori Arti yang dikemukakan oleh Leech (1974).Hasil penelitianmenemukan bahwa terdapat 14 kalimat dari enam jenis bahasa kiasan yang digunakandalam lagu-lagu Ed Sheeran Selected, seperti simile dengan 2 atau 14%, metaforadengan 1 atau 8%, personifikasi dengan 3 atau 21%, metonimi dengan 1 atau 8%,hiperbola dengan 5 atau 35%, ironi dengan 2 atau 14%. Dapat diindikasikan bahwa jenismajas yang dominan dalam lirik lagu adalah hiperbola. Makna bahasa kiasan juga dapatdinyatakan dengan jelas. Dapat disimpulkan bahwa bahasa kiasan memiliki peranpenting dalam menciptakan lirik lagu. Menggunakan bahasa kiasan membuat lagu lebihmenarik. Itulah sebabnya penulis menggunakan kalimat-kalimat yang memiliki bahasakiasan dalam lagu tersebut.Kata Kunci: Bahasa kiasan, lirik lagu dan maknanya